Numerical Study on the Particle Flow Behavior of Bolted Jointed Rock Mass under Impact-Shear Coupling - Zhang, Qingshui (International Journal of Natural Resources and Environmental Studies, 2026)
To clarify the shear mechanical response and crack evolution of bolted jointed rock masses under impact disturbance, a mesoscopic particle flow model of the “rock mass-joint-bolt” system was established using PFC2D. The mechanical behavior and damage evolution of bolted jointed rock masses under impact-shear coupling were systematically investigated under different impact numbers, impact patterns, and confining pressures. The results show that, after impact disturbance, the shear stress-shear displacement curve of the bolted jointed rock mass can be divided into four stages: elastic stage, stress-drop stage, strengthening stage, and residual stage, while the normal displacement-shear displacement curve undergoes three stages: shear contraction, dilation, and softening. With the increase in impact parameters, the shear modulus, peak shear stress, and residual strength generally decrease, the normal restraint capacity weakens, the joint closure increases, and the peak normal displacement decreases. With increasing confining pressure, the shear strength and residual bearing capacity are enhanced, whereas the dilation behavior is significantly restrained. Based on the evolution law of normal displacement, the peak dilation angle was defined and its degradation characteristics were analyzed. The results indicate that the peak dilation angle generally shows a trend of initial increase followed by decrease with increasing impact parameters, while its attenuation coefficient increases with confining pressure. Crack evolution analysis further shows that impact disturbance significantly promotes internal crack propagation in bolted jointed rock masses, and the number of cracks increases with impact parameters. As confining pressure increases, the total number of cracks further increases, whereas the proportion of tensile cracks decreases slightly. The study can provide a reference for the stability analysis and support design of bolted jointed rock masses subjected to impact disturbance.